Vancomycin-intermediate resistance in Staphylococcus aureus. Issue 4 (December 2014) - Hiramatsu, Keiichi; Kayayama, Yuki; Matsuo, Miki; Aiba, Yoshifumi; Saito, Michie; Hishinuma, Tomomi; Iwamoto, Akira
Abstract: Vancomycin-intermediate Staphylococcus aureus (VISA) and its precursor hetero-VISA (hVISA) were discovered almost 20 years ago and have continued to be a stumbling block in the chemotherapy of methicillin-resistant S. aureus (MRSA). Unlike vancomycin resistance mediated by the van gene in enterococci and staphylococci, VISA is generated by accumulation of mutations. It displays diverse and intriguing genetic mechanisms underlying its resistance phenotype. Here we make a brief note on our recent understanding of the genetics of hVISA, VISA and the newly discovered phenotype 'slow VISA' (sVISA).